Diagnosis of the status of the anuran collection at La Salle Museum, Bogotá, Colombia - Julieth Stella Cárdenas Hincapie; Diana Alexandra Delgadillo Méndez (Biota Colombiana, 2019)
The anuran collection of the Museo de La Salle is one of the oldest in Colombia, with 2059 specimens collected since 1917. Its age represents a challenge for a thorough quantification of its status, considering that it may not necessarily fit current quality standards. Therefore, we implemented a methodology to evaluate the status of the collection in terms of health, data completeness, taxonomic representativeness, taxonomic identification and geographical coverage. The collection harbors 13 families, with Craugastoridae as the best represented, with 44 species and 517 specimens. The department with the largest number of specimens was Cundinamarca, with 363 records of 52 species. Most specimens are in optimal condition of conservation and preservation. The results of this research enabled the solution of problems in the collection and it could be useful for other collections.